Tópicos de Dinâmica Hiperbólica - DINIZ, Diego Araújo (2017)
The main goal of this work is to discuss some topics about hyperbolic dynamical systems. We collect results and definitions that are dispersed, or even in works of generalized context. Thus, we propose a tour that begins with the definition of orbit, passes through classical results like Hartman-Grobman Theorem and shadowing lemma, and ends with the Omega stability theorem.